Metode Pembacaan Turâts Arab-Islam: Perspekti Muhammad ‘Abid al-Jâbirî - Abdul Mukti Ro’uf (Ulumuna, 2010)
The way how turâts (a term only found in contemporary Arabic-Islam or tradition) is viewed has been a critical problem. This is because queries about it imply rise and or fall of a civilization. This thesis has at least been proved by facts of history that since the midst 19th century the world of Arabic-Islam thoughts have been moving backward compared to that in the Western-modern thoughts. This research will analyze Muhammad ‘Âbid al-Jâbirî’s thoughts that represented contemporary thinkers. Al-Jâbirî was a muslim intellectual born in Feiji Southeast-Marocco in 1936. His initial acquaintance with philosophical thoughts related to three prominent figures of Karl Marx (1818-1890), Gaston Bachelard (1884-1962), and Louis Althusser (1918-1990). He was grown up in a setting of Maghribi thoughts (Marocco-Andalusia), which was influenced by traditions of French philosophy of Marxian. However, he doubted Marxian approaches in Islamic history context.